Activity of lysosomal urine enzymes in children after acute kidney injury - I.V. Bagdasrova; L.V. Korol; O.V. Lavrenchuk; L.Ya. Migal (Ukrainian Journal of Nephrology and Dialysis, 2019)
The importance of the problem of acute kidney injury in children is due to the high risk of developing chronic kidney disease as a consequence. Lysosomal enzymes of β-galactosidase (GAL) and N-acetyl-β-D-hexozoaminidase (NAG) in urine are considered to be informative markers of renal parenchyma damage. The objective of this study - to determine the activity of lysosomal enzymes in urine as markers of progression of interstitial nephritis in children after acute kidney injury.Methods. 41 children were examined after acute kidney injury, achievement of self-diuresis and improvement. Group I included 22 patients with a disease period of up to 2 years after acute kidney injury, group II - 19 patients with a disease period of 2 years or more. The control (reference) group consisted of 28 children who were conditionally healthy, without kidney disease, as well as without acute diseases and severe metabolic disorders and anatomical defects.Results. NAG and GAL activity were found to exceed 8 and 3 times parameters in the reference group of healthy children, respectively, in patients who had acute kidney injury during the year (p <0.001). In patients with a history of 2 years or more, enzyme levels decreased, but remained higher than normal up to 4 times (p <0.001). The highest level of NAG activity was observed in patients of group 1 with the combination of hemolytic-uremic syndrome with hemolytic anemia, and the lowest - in children with toxic kidney.Determination of the activity of lysosomal enzymes NAG and GAL is a more informative marker of torpid course of interstitial nephritis with a progressive decrease in renal function than indicators of glomerular filtration rate. In twelve months after acute kidney damage in 75% of children, the level of NAG and GAL activity remained significantly elevated at normal glomerular filtration rate. A correlation between glomerular filtration rate and NAG activity (r = -0.473) and GAL (r = -0.333) and a direct correlation between NAG and GAL activity (r = 0.845) were observed.Conclusions. The levels of lysosomal enzymes of NAG and GAL were found to be 8 and 3 times higher than normal, respectively, in patients who suffered acute kidney injury during the year, and in patients with a history of 2 years or more, enzyme activity levels decreased, but remained higher than normal 4-fold (p <0.001). In a year after acute kidney damage in 75% of children, the level of NAG and GAL activity remained significantly elevated despite of normal glomerular filtration rate. Therefore, the detection of NAG and β-galactosidase in the urine of children after acute kidney injury are informative markers of renal parenchyma damage, which may serve as objective criteria for progressive decline in renal functional status, and the lack of normalization of their levels is not a sign of progression of interstitial nephritis in corresponding group of children.